Mastering Business Communication - Macmillan; Unwin R. W; Woolcott A. L (1983)
All the essential information to learn and master business communication. Introduction, Correspondence, Reports, Summarizing, Advertising and Publicity, Manuals and Instructions and Form Design, Meetings Documentation, Meetings, Spoken Communication, Listening and Reading, The Role of Audio-Visual Aids, Thinking and Planning, Language, Non-Verbal Communication, Charts and Graphs, Analysis and Interpretation, External and Internal Communication, Management Communication, Information Technology - The Future, Appendices, Index.